Confocal laser scanning microscopy investigation of bond interfaces involved in fiber glass post cementation - Ticiane Cestari Fagundes; Daniele Salazar Somensi; Paulo Henrique dos Santos; Maria Fidela Lima Navarro (Brazilian Dental Science)
Objective: This confocal microscopy study evaluated the cement/dentin and cement/post interfaces along the root canal walls when fiber glass posts were bonded to dentin using different types of cements.